Energy efficient spectrum sensing for cognitive radio network using artificial bee colony algorithm - Eappen, Geoffrey; T. Shankar, Dr (International Journal of Engineering and Technology, 2018)
In this paper Artificial Bee Colony (ABC) algorithm based optimization of energy efficiency for spectrum sensing in a Cognitive Radio Network (CRN) is implemented. ABC algorithm which is an efficient optimization technique is used for optimizing energy efficiency func-tion derived for cognitive users, where energy efficiency function is derived as the dependency on spectrum sensing time and the transmis-sion power. Energy efficiency optimized by ABC is compared with Particle Swarm Optimization (PSO) based technique. Simulation results shows that with ABC it is able to achieve more energy efficient spectrum sensing as compared to PSO optimized with a margin of 33% efficiency over PSO.Â Â